Assessment of Commercial DNA Extraction Kits for Porcine Gelatin Detection Using RT-PCR and ddPCR - Gina, Safira; Rahmagiarti, Cintera; Ummah, Isna Mustafiatul; Sumantri, Cece; Suparto, Irma Herawati; Darmawan, Noviyan (Science and Technology Indonesia, 2024)
Gelatin is extensively applied in various industries, including food, beverages, cosmetics, and pharmaceuticals. Although the determination of gelatin species is essential for religious, health, and consumer preference reasons, a standardized analysis method is absent. The challenge in identifying gelatin through DNA-based methods arises from the low DNA content and extensive DNA denaturation in the gelatin matrix. This study assessed the efficacy of two commercial DNA extraction kits, namely the Processed Food DNA Extraction (PF kit) and the DNeasy Mericon Food Kit (DM kit), for extracting DNA from porcine gelatin powder and commercial products derived from gelatin. Additionally, we evaluate the amplification of the extracted porcine DNA using real time polymerase chain reaction (RT-PCR) and droplet digital polymerase chain reaction (ddPCR) techniques. The PF extraction kit demonstrated successful DNA extraction from porcine gelatin powder and commercial samples of porcine gelatin-based candies with a higher concentration (32.24-286.07 ng/uL) and purity (A260/A280 ratio of 1.82-2.33) compared to the DM kit (3.95-7.30 ng/uL and an A260/A280 ratio of 1.29-2.45). RT-PCR and ddPCR analyses yielded positive results for porcine DNA from gelatin powder for both PF and DM kits, albeit with differing Cq values and copy numbers. The choice of DNA extraction kit significantly impacted the amplification results when analyzing commercial samples of porcine gelatin-based candies. Using RT-PCR, all samples yielded negative results with the DM kit, while the PF kit detected one positive result for porcine DNA. Improved outcomes were observed with more sensitive analysis methods such as ddPCR, where the DM kit identified one positive result for porcine DNA while the PF kit detected positive results for all tested candies.